The Mediating Role of Brand Trust in the Effect of Service Quality on Brand Loyalty : A Study at PT Bukit Vista Nusantara - I Made Ganes Arta Nugraha; Ni Made Rastini (International Forum of Researchers and Lecturers, 2025)
In the competitive property management industry, a company’s success depends not only on attracting new partners but also on retaining existing ones through strong brand loyalty. PT Bukit Vista Nusantara faces challenges in sustaining partner loyalty, as indicated by the high number of partners terminating their collaboration within a short period. This study aims to analyze the effect of service quality on brand loyalty, with brand trust serving as a mediating variable. A quantitative associative approach was employed involving 62 active partners who had collaborated with the company for more than one year, selected using purposive sampling. Data were collected through questionnaires and analyzed using path analysis and the Sobel test to assess mediation. The results show that service quality has a positive and significant effect on both brand trust and brand loyalty. Brand trust also significantly strengthens brand loyalty and mediates the relationship between service quality and brand loyalty. These findings underscore the importance of building brand trust to enhance long-term partner loyalty.